Local exciton ground states in disordered polymers - Makhov, D; Barford, W (2010)
Exciton localization in conjugated polymers with weak conformational disorder is investigated via the Anderson model with Gaussian off-diagonal disorder, σ. We show that a small fraction of the low-energy eigenstates are spatially localized, nonoverlapping, and space filling. We term these states "local exciton ground states" (LEGS). The LEGS exhibit an almost Gaussian density of states, an average localization length L∼ σ-2/3, and an inhomogeneous optical linewidth ∼ σ4/3 Their transition dipole moments scale with their localization length in a way consistent with a lowest energy excitation confined to a region ∼O (L). The length scale over which the LEGS are confined is an effective low-energy conjugation length or spectroscopic segment. The appendix describes an efficient and accurate technique for calculating the density of states of the Anderson model. © 2010 The American Physical Society.